INFLUENCE ANTIOMOTOXIC PREPARATIONS ON UNSPECIFIC REACTION OF ADAPTATION OF ORGANISM (World Science, 2021)
Effectiveness of Heel firm antihomotoxic preparation on unspecific adaptation reactions of organism was studied in this work. The main work was being done on the base of Georgian LLS of Physical Culture and on the base of Center of Treatment, Tbilisi. 57 patients 19-58 of age were taken for the investigation. They were divided into two groups. Group A (30 person) was prescribed antiohomotoxic preparations dosage according to general rules of usage of Heel firm preparation. Control and correction of the dosage of Heel firm preparation was making of croup B (27 persons) once a week. By its phone parameters of white blood group A and B didn’t have truthfully differences (p˃0,05). The possibility to model the resistance of organism with putting an antihomotoxic preparation was established with using of parameters of white blood. The new approach to individual dosage of antihomotoxic preparation was worked out in treatment of such diseases as gastritis, colitis, cystitis, adnexitis, thrombophlebitis, bronchial asthma, arthritis.